Experimental and theoretical investigation of stable diastereomeric conformations of biscarboline amides in solution. Issue 31 (2nd August 2018) - Liang, Miao-Miao; Ma, Yang-Yang; Zhu, Liang; Jia, Yun-Jing; Zhu, Hua-Jie; Li, Wan; Zhou, Bei-Dou
Abstract: Stable axial conformations generally exist only when the single bond's (axis') rotation was sterically hindered in solution. Herein, we firstly show that two stable conformations could be observed in solution by 1 H and 13 C NMR experiments when the single bond rotates freely. Its coalescence temperature was measured up to 120 °C when we took compound 13 as an example. The ratio of the two stable conformations was computed using quantum methods. The predicted results matched with the experimental results well. The conversion barrier between two conformers was estimated by potential energy scan (PES) and transition state (TS) calculations at the B3LYP/6-311 + G(d) level. Furthermore, its stereochemistry was also well studied by comparing theoretical electronic circular dichroism (ECD) spectra with the experimental one. Graphical abstract: Image 1